Durable Machine-Washable Wool via AOX-Free Plasma-Mediated Coating with Keratin - Marwa Abou-Taleb; Hosam El-Sayed (Journal of Natural Fibers)
Although their favorable performance, appearance, and comfort attributes, woolen garments have the tendency to felt unenviably during washing. In this work, an eco-friendly, energy-saving, non-deteriorative process for the fabrication of machine-washable wool tops (WTs) was proposed. WTs were exposed to atmospheric air or an argon plasma treatment at different powers for various durations, followed by coating with a protein biopolymer, namely keratin, using the pad-dry-cure technique. The felting resistance of the finished WTs was evaluated, and the results revealed that the finished sample has an enhanced felting resistance to the extent of machine-washable wool (no felt ball is formed), whereas the untreated sample forms a felt ball with a diameter of 2.166 cm after undergoing the felting test. The treated WTs maintained their felting resistance after 20 wash cycles. The surface composition of the plasma-treated WTs was examined using X-ray photoelectron spectroscopy. The change in the chemical structure of the treated WTs was monitored by determining the cystine content, alkali solubility, base-combining capacity, and affinity to anionic dye. The dye exhaustion of the untreated and finished samples after 60 min was 66% and 98.8%, respectively. Scanning electron microscopy was used to study the wool fibers’ topography.